PENGARUH PENGGUNAAN TEKNIK UKIR ALUMINIUM TERHADAP KREATIVITAS SENI RUPA SISWA SEKOLAH DASAR - Ainurrafa, Shafira; Nurmeta, Irna Khaleda; Maula, Luthfi Hamdani (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2025)
Creativity is one of the essential aspects in visual arts education, thus requiring innovative approaches to enhance it. This study aims to examine the effect of aluminum engraving techniques on elementary school students’ creativity in visual arts. The research used an experimental method with a population consisting of all sixth-grade students at SDN Selajambe 01 during the first semester of the 2024/2025 academic year, totaling 33 students. Data were collected through tests using performance sheets, and data analysis involved descriptive statistics, prerequisite tests, and hypothesis testing. The results showed a significant difference between pre-test and post-test scores in both groups. The experimental group showed an increase in the average score from 53.65 to 79.00, with a percentage gain of 47%, while the control group improved from 49.00 to 62.71, with a gain of 28%. This was further supported by the hypothesis test results, where the post-test scores between the two groups showed a significant difference with a Sig. (2-tailed) value of 0.000. Since the obtained value is lower than the predetermined significance level of 0.05, the null hypothesis (H?) was rejected, and the alternative hypothesis (H?) was accepted. Thus, it can be concluded that the use of aluminum engraving techniques has a significant effect on students’ creativity in visual arts at the elementary school level. This technique not only fosters students' creativity but also provides them with a new and engaging learning experience.